An evaluation of product diversification as a survival strategy: a case study of Comhold Services - Chidziwo, Don (Midlands State University, 2014)
This research sought to evaluate product diversification as a survival strategy, using a case of Comhold Services.Chapter one has the background of the study the research objectives, the significance of the study, limitations, delimitations and definition of key terms. The objectives were to evaluate if diversification can be relied upon as a survival strategy, to determine the impact of related diversification on company profitability and to determine the impact of unrelated diversification on company profitability. These objectives were aligned with the research questions to answer the core issues. Major thoughts, ideas and concepts of different scholars were reviewed using books, previous thesis included text books, electronic journals and Comhold company records. The concepts and thoughts of these scholars were of much help in completing this research study as the researcher managed to identify knowledge gaps and close them using the ideas of other authors. The researcher compared and contrasted the contributions of various authors to find points of convergence and divergence.Exploratory and descriptive researches were both used to carry out the research. The target population of the research was management; employees and customers of Comhold Services specifically in Harare,and the research instruments used were questionnaires and interviews.The researcher used a sample size of 30 respondents. While Microsoft Excel was used to analyse quantitative data, content analysis and thematic were used to analyze qualitative data. The data collected from these research instruments were presented, analyzed and interpreted from the data presentation techniques pie chart, bar graphs and tables for easy drawing of conclusions. The conclusions drawn from the findings are: Diversification indicates to be effective as a survival strategy. Therefore the researcher recommends its adoption in a harsh economic environment. The researcher also recommends that a similar study be carried out evaluate the effectiveness of other survival strategies on a company in a different industry.